2020
DOI: 10.3390/nu12030858
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing Low and High Water Consumers—A Paradigm of Disease Risk

Abstract: A long-standing body of clinical observations associates low 24-h total water intake (TWI = water + beverages + food moisture) with acute renal disorders such as kidney stones and urinary tract infections. These findings prompted observational studies and experimental interventions comparing habitual low volume (LOW) and high volume (HIGH) drinkers. Investigators have learned that the TWI of LOW and HIGH differ by 1–2 L·d−1, their hematological values (e.g., plasma osmolality, plasma sodium) are similar and li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 136 publications
(290 reference statements)
5
24
0
1
Order By: Relevance
“…If salt depletion is suspected (e.g., increased salt appetite or salt craving), it is prudent to consider adding specific dietary food items to ensure that daily sodium intake replaces exercise-induced sodium loss. Refer to [97] to identify the amount of sodium in common food items. Sodium supplementation during meals should be guided by dietary recommendations for daily sodium intake [127], and by considering the potential negative health effects of chronic high dietary salt intake [128].…”
Section: Rehydration Recommendations For Endurance Athletesmentioning
confidence: 99%
See 2 more Smart Citations
“…If salt depletion is suspected (e.g., increased salt appetite or salt craving), it is prudent to consider adding specific dietary food items to ensure that daily sodium intake replaces exercise-induced sodium loss. Refer to [97] to identify the amount of sodium in common food items. Sodium supplementation during meals should be guided by dietary recommendations for daily sodium intake [127], and by considering the potential negative health effects of chronic high dietary salt intake [128].…”
Section: Rehydration Recommendations For Endurance Athletesmentioning
confidence: 99%
“…However, as shown in Figure 5 , the P osm threshold at which thirst is perceived varies greatly across individuals (range, 274–293 mOsm/kg) and may be lower than the range of laboratory reference values for P osm (285–295 mOsm/kg) [ 96 ]. The data in Figure 5 were compiled from 5 published human studies; the shape of this frequency distribution implies that the thirst threshold is a multifactorial (polygenic) characteristic [ 97 ]. Although inter-individual differences of the P osm threshold for thirst have not been studied during exercise, Figure 5 suggests that the level of dehydration (i.e., increased P osm ) that initiates drinking during exercise might differ considerably among athletes.…”
Section: The Complexity Of Thirst and Drinkingmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, other researchers [51] have noted that the specific gravity, color, and osmolality of urine have been widely advocated for screening of dehydration in older adults and that, as a result, these measures should not be used to indicate hydration status in older people (either alone or as part of a wider tranche of tests). In a recent study, Armstrong et al [52] concluded that low volumes differed from high volumes in terms of urinary biomarkers (e.g., reduced urine volume and increased osmolality or specific gravity) and that a self-assessment of urine color provided useful feedback regarding excessive drinking.…”
Section: Fluid Intake Of the Elderlymentioning
confidence: 99%
“…Although some studies have reported no difference in serum osmolality between habitually low fluid intake and high fluid intake [ 13 ], even a slight increase in serum osmolality was found to stimulate the release of arginine vasopressin and cortisol, which are known to heighten the risk of chronic diseases. In clinically stable long-term care residents, elevations of serum osmolality were frequently observed without clinically overt signs of dehydration [ 14 ], so using serum osmolality to assess chronic dehydration is considered reasonable.…”
Section: Introductionmentioning
confidence: 99%